Health care providers counselling of caregivers on their children’s condition at Usmanu Danfodiyo university teaching hospital, Sokoto, North-Western Nigeria - Dr. Adamu Asma’u; Dr. Isezuo Khadijat Omeneke; Dr. Sani Usman M.; Dr. Ibitoye Paul Kehinde; Dr. Modupe Omoshalewa Ugege; Dr. Bilkisu Ilah Garba; Dr. Muhammad Ali; Dr. Umar Mohammad Ango; Dr. Jiya BF. (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Counselling of caregivers about common childhood diseases is an important component of health care services. Objective: To assess the quality of counselling offered to caregivers on their children’s condition by health care providers at Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto.Methods: A prospective cross-sectional study carried out from 1st August 2015 to 30th April 2016. Caregivers with children less than 15 years of age seen in the units of Paediatric Department of UDUTH, Sokoto, were consecutively interviewed. The corresponding case notes of their children were reviewed to obtain data on the child’s diagnosis and to check whether the attending physicians have documented the content of the counselling offered to caregivers. Data were analysed using SPSS version 20.Results: A total of 420 caregivers were interviewed. Their mean age was 28.9±8.6 years (range of 15-64 years). Only 218 (51.9%) caregivers were counselled, but there was no documentation of the content of counselling in the case notes of their children. 81 (37.2%) of the diagnosis mentioned by caregivers did not tally with the one documented in the case notes of their children (p=0.0001). Majority of the caregivers 156 (71.6%) were counselled in an open ward and only 6 (2.7%) were counselled in a private consulting room.Conclusion: This study revealed inadequate counselling of caregivers on their children condition and poor counselling practices among healthcare providers in UDUTH, Sokoto. Hence, there is the need for training and retraining of healthcare providers on counselling of caregivers on their children condition in the hospital.